2014
DOI: 10.5604/12321966.1120616
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year secular trend of overweight and obesity in school children in south-eastern Poland

Abstract: A trend toward stabilization of the prevalence of overweight and obesity was noted in school children from south-eastern Poland between 1998-2008. The declining prevalence of obesity in girls and increased prevalence of overweight in boys demonstrates that in this age group of children the secular trend is gender dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 19 publications
3
25
1
Order By: Relevance
“…The data concerning anthropometric measurements such as height, weight, and BMI showed diversity according to age and gender. Similar values for growth, body weight, and the mean values of BMI were found in previous Polish studies among a group of children and adolescents in 2007-2009 [12,13], but we found a lower proportion of overweight children, and a higher proportion of children with obesity compared to previous studies [12]. Another Polish study [14], which examined the prevalence of overweight and obesity among adolescents aged 13-15 years in 2005, reported a lower percentage of adolescents with overweight and obesity in both genders.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The data concerning anthropometric measurements such as height, weight, and BMI showed diversity according to age and gender. Similar values for growth, body weight, and the mean values of BMI were found in previous Polish studies among a group of children and adolescents in 2007-2009 [12,13], but we found a lower proportion of overweight children, and a higher proportion of children with obesity compared to previous studies [12]. Another Polish study [14], which examined the prevalence of overweight and obesity among adolescents aged 13-15 years in 2005, reported a lower percentage of adolescents with overweight and obesity in both genders.…”
Section: Discussionsupporting
confidence: 87%
“…Participants of both genders (13)(14)(15)(16)(17)(18)(19) years old, n = 14,044 students) were recruited from 207 randomly selected schools. The information about the possibility of joining the program was sent to all schools listed in the electronic register of schools of the Minister for National Education…”
Section: Study Participantsmentioning
confidence: 99%
“…9,10 Other jurisdictions (e.g., Poland, Australia, the Netherlands, Germany and Denmark) have shown variable changes with either small declines or plateaus in obesity rates. [11][12][13][14][15] Some developing countries are undergoing the same surge in obesity witnessed in Canada from 1978 to 2004. 16 Other investigators have identified higher rates of obesity among Canadian boys using self-reported measures.…”
Section: Discussionmentioning
confidence: 99%
“…4 Results from the United States have shown a decline in obesity rates among toddlers and a plateau in rates among older children; 9,10 stabilization has also been noted in other jurisdictions (e.g., Germany and Australia). [11][12][13][14][15][16] We undertook this study to determine the most recent trends in the prevalence of overweight and obesity among Canadian children using the current WHO weight charts for Canada applied to a representative sample of children.…”
mentioning
confidence: 99%
“…The results obtained in 2009 revealed a further increase in the percentage of overweight and obese children, reaching 35% in boys and almost 20% in girls [4]. In 2008 in south-eastern Poland, the prevalence of overweight was 13.3% in girls and 14.2% in boys, whereas the prevalence of obesity was 7.7% in girls and 6.4% in boys [5].…”
Section: Introductionmentioning
confidence: 91%